Pengelolaan Bahaya Kehidupan Liar melalui Sistem Pengendalian Satwa Liar di Bandara - M. Indra Martadinata; Bambang Wijaya Putra; Rinto Astutik; Fitri Masito (Airman: Jurnal Teknik dan Keselamatan Transportasi, 2022)
This study aims to analyze systemm control of wild animals and the process of solving problems of controlling wild animals at Taufik Kiemas Airport, Pesisir Barat, Lampung Province based on public perception.This research was conducted at Taufik Kiemas Pesisir Barat Airport, Lampung Province in August 2022. In this study, the researcher used a descriptive type of research with a qualitative approach. This study uses one data source, namely primary data sources obtained through surveys. The sampling method is purposive sampling. In this study there were 19 people who became the research sample. The data analysis technique used descriptive qualitative analysis which attempted to describe the nature of the problems studied which were carried out in the field at the time of data collection. The results showed that the presence of wild animals such asbobcats, monkeys, wild boars, monitor lizards, snakes, various birds, monkeys and othersin Banfrom Taufik Kiemas Airport, West Coast of Lampung Province. Therefore it is necessary to create a special unit that handles the presence of wild animals at the airport and regulations are needed that are understood by all employees. In an emergency caused by wild animals, officers must understand how to mitigate the risk, so training and socialization are needed in understanding the presence of wild animals at airports.